2011
DOI: 10.3109/13561820.2011.595849
|View full text |Cite
|
Sign up to set email alerts
|

“Knowing more about the other professions clarified my own profession”

Abstract: The purpose of this study was to compare which learning outcomes relating to an Interprofessional Training Unit (ITU) experience were found to be most important by students and by alumni. A cohort of 428 students in the ITU was asked to write three short statements describing the most important learning outcomes from the ITU. Alumni from the same cohort were after graduation asked the same question. Furthermore, they were asked to fill out a 12-item questionnaire. The statements concerning learning outcome wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 17 publications
3
23
0
4
Order By: Relevance
“…The findings suggest that students had developed understanding of other discipline roles, better understood their own roles, and appreciated the role of teamwork. These findings were supportive of other studies of two-to-three week IPE in Sweden (Hallin et al 2009, Lidskog et al 2009), Canada (Charles 2004) and Denmark (Jakobsen et al 2011). A follow-up study by Jakobsen et al (2011) of graduates who had completed an IPE placement as students found that these graduates perceived that the learning experience was more valuable in their longer term development of interprofessional and professional identity than they had recognised when they were students.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…The findings suggest that students had developed understanding of other discipline roles, better understood their own roles, and appreciated the role of teamwork. These findings were supportive of other studies of two-to-three week IPE in Sweden (Hallin et al 2009, Lidskog et al 2009), Canada (Charles 2004) and Denmark (Jakobsen et al 2011). A follow-up study by Jakobsen et al (2011) of graduates who had completed an IPE placement as students found that these graduates perceived that the learning experience was more valuable in their longer term development of interprofessional and professional identity than they had recognised when they were students.…”
Section: Introductionsupporting
confidence: 84%
“…These findings were supportive of other studies of two-to-three week IPE in Sweden (Hallin et al 2009, Lidskog et al 2009), Canada (Charles 2004) and Denmark (Jakobsen et al 2011). A follow-up study by Jakobsen et al (2011) of graduates who had completed an IPE placement as students found that these graduates perceived that the learning experience was more valuable in their longer term development of interprofessional and professional identity than they had recognised when they were students. Fortune et al (2013) opined that in order to prepare graduates for health professional practice in a 'supercomplex world', undergraduate programmes now need to develop innovative transitional fieldwork experiences characterised by self-direction, collaboration and negotiation.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Students from the involved professions form an interprofessional team and under supervision from trained interprofessional staff provide care and rehabilitation to patients admitted for planned arthroplasty of the hip or knee (Jacobsen, Fink, Marcussen, Larsen, & Hansen, 2009). Simultaneously with learning interprofessional collaboration and respect for the other professions, the students strengthen their own professional identity including self-efficacy and uniprofessional knowledge and capability (Jakobsen, Hansen, & Eika, 2011). …”
Section: Introductionmentioning
confidence: 98%
“…Both the intervention group and the control group scored the RIPLS subscale ''professional identity'' significantly higher after, compared to before, the course on the IPTW, a finding also supported by our interview data. An increase in the clarity of one's own professional identity is probably related to the impact of the IPTW placement itself, as also previously reported by Jacobsen, Baek Hansen, and Eika (2011). We compared the students' RIPLS ratings before and after the course and showed that the students who had used CASS rated their readiness for teamwork and collaboration via RIPLS significantly higher after the IPTW course than before it, a difference that was not noted in the control group.…”
Section: Discussionmentioning
confidence: 52%